On l1-gain control for 2D delayed positive systems in FM LSS models: necessary and sufficient conditions. Issue 16 (10th December 2022) - Duan, Zhaoxia; Han, Yuchen; Xiang, Zhengrong; Ghous, Imran
Abstract : This paper presents an l 1 -gain control design for two-dimensional (2D) delayed positive systems (PSs) in the Fornasini-Marchesini local state-space model. First, for a stable 2D delayed PS, the necessary and sufficient conditions are derived for the calculation of the exact value of the l 1 -gain. Then, the controller design is given with the aid of the singular value decomposition method, which ensures that the closed-loop system is asymptotically stable at the specified l 1 -gain level. In the end, two examples are provided to identify the validity and correctness of the results of the theory.